2017
DOI: 10.1016/j.pbb.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in abuse-related neurochemical and behavioral effects of 3,4-methylenedioxymethamphetamine (MDMA) in rats

Abstract: 3,4-methylenedioxymethamphetamine (MDMA) is a substrate for the dopamine (DA), norepinephrine and serotonin (5HT) transporters that produces greater pharmacological effects on certain endpoints in females than males in both clinical and rodent preclinical studies. To evaluate potential for sex differences in abuse-related MDMA effects, the present study compared MDMA effects on intracranial self-stimulation (ICSS) and on in vivo microdialysis measurements of DA or 5HT in the nucleus accumbens (NAc) in female a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…Therefore, we started comparing DA and 5-HT basal outputs in male and female rats, and we did not observe any differences in any of the brain areas studied (i.e., NAc shell and core and the mPFC), in agreement with previous microdialysis studies aimed at CPu of male and female groups (Xiao and Becker, 1994). Oppositely, Lazenka et al (2017) observed a lower baseline NAc DA levels in female compared to male rats. Results obtained by monitoring estrous cycle in female rats suggested that, although the treatment affected significantly the DA transmission in all A and B) and on core temperature (c and D) and tail pinch test (e and F).…”
Section: I-nbome Affects the Dopaminergic Transmission In The Nac Ssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, we started comparing DA and 5-HT basal outputs in male and female rats, and we did not observe any differences in any of the brain areas studied (i.e., NAc shell and core and the mPFC), in agreement with previous microdialysis studies aimed at CPu of male and female groups (Xiao and Becker, 1994). Oppositely, Lazenka et al (2017) observed a lower baseline NAc DA levels in female compared to male rats. Results obtained by monitoring estrous cycle in female rats suggested that, although the treatment affected significantly the DA transmission in all A and B) and on core temperature (c and D) and tail pinch test (e and F).…”
Section: I-nbome Affects the Dopaminergic Transmission In The Nac Ssupporting
confidence: 86%
“…Sex differences have been reported in the initiation of drug use, affecting the continuation of drug use as well as the phases of abstinence and relapse (Becker and Hu, 2008;Fattore et al, 2010), but also in the codification of reinforcement and related cues (Zlebnik, 2019). The greater increase of DA extracellular levels in females compared to males is consistent with previous studies reporting that amphetamine (Virdee et al, 2014), cocaine (Holly et al, 2012), and MDMA (Lazenka et al, 2017) are more effective in increasing DA release in the NAc of female rats. The reason for these neurochemical sex discrepancies has been historically ascribed to deep biological differences, such as sex dimorphisms in the anatomy of DArgic systems in areas like SN and VTA (Walker et al, 2012), as well as ovarian hormone fluctuations (Becker and Hu, 2008).…”
Section: I-nbome Affects the Dopaminergic Transmission In The Nac Ssupporting
confidence: 84%
“…A potential limitation of the ICSS experiment was the lack of baseline testing of the mice prior to sugar exposure, which is a technically demanding experiment due to long-term electrode maintenance (8 weeks). Furthermore, since previous ICSS studies do not report any sex differences under naïve baseline conditions 39 , 40 , we found it reasonable not to test ICSS prior to sugar exposure.…”
Section: Discussionmentioning
confidence: 90%
“…A potential limitation of the ICSS experiment was the lack of baseline testing of the mice prior to sugar exposure, which is a technically demanding experiment due to long-term electrode maintenance (8 weeks). Furthermore, since previous ICSS studies do not report any sex differences under naïve baseline conditions (Faunce and Banks, 2020;Lazenka et al, 2017), we found it reasonable not to test ICSS prior to sugar exposure.…”
Section: Discussionmentioning
confidence: 92%